The endocytic pathway acts downstream of Oskar in Drosophila germ plasm assembly. - Tanaka, T.; Nakamura, A. (Development, 2008)
Cell fate is often determined by the intracellular localization of RNAs and proteins. In Drosophila oocytes, oskar (osk) RNA localization and the subsequent Osk synthesis at the posterior pole direct the assembly of the pole plasm, where factors for the germline and abdomen formation accumulate. osk RNA produces two isoforms, long and short Osk, which have distinct functions in pole plasm assembly. Short Osk recruits downstream components of the pole plasm, whose anchoring to the posterior cortex requires long Osk. The anchoring of pole plasm components also requires actin cytoskeleton, and Osk promotes long F-actin projections in the oocyte posterior cytoplasm. However, the mechanism by which Osk mediates F-actin reorganization remains elusive. Furthermore, although long Osk is known to associate with endosomes under immuno-electron microscopy, it was not known whether this association is functionally significant. Here we show that Rabenosyn-5 (Rbsn-5), a Rab5 effector protein required for the early endocytic pathway, is crucial for pole plasm assembly. rbsn-5(-) oocytes fail to maintain microtubule polarity, which secondarily disrupts osk RNA localization. Nevertheless, anteriorly misexpressed Osk, particularly long Osk, recruits endosomal proteins, including Rbsn-5, and stimulates endocytosis. In oocytes lacking rbsn-5, the ectopic Osk induces aberrant F-actin aggregates, which diffuse into the cytoplasm along with pole plasm components. We propose that Osk stimulates endosomal cycling, which in turn promotes F-actin reorganization to anchor the pole plasm components to the oocyte cortex.